ANCA positive relapsing polychondritis, Graves disease, and suspected moyamoya disease: A case report. Issue 51 (December 2017) - Xuan, Yi-Yi; Li, Tian-Fang; Zhang, Lei; Liu, Sheng-Yun
Abstract: Ratioinale: Relapsing polychondritis (RP) is a rare and heterogeneous disease complex of unknown origin which basically affects cartilaginous structures, 40% of which accompanied by rheumatic, hematologic, and endocrine disease. Among them, vasculitis is the most common accompanying type and usually presented with positive antineutrophilic cytoplasmic antibody (ANCA). The presence of ANCA could be primary or drug-induced like propylthiouracil (PTU). Central involvement of RP is very rare, and there is almost no report of cerebral vasculopathy manifested as moyamoya. Patient concerns: A 26-year-old woman complained about recurrent fever, auricular chondritis, ocular inflammation, and arthritis. She had an 8-year drug intake of PTU for Graves disease. Myeloperoxidase antineutrophilc cytoplasmic antibodies (MPO-ANCA) were found positive. Magnetic resonance angiography (MRA) detected multiple intracranial vasculopathy which we highly suspected it as moyamoya disease. Diagnoses: Relapsing polychondritis, Graves disease and suspected moyamoya disease were clinically diagnosed. Interventions and outcomes: In case of possible PTU-induced vasculitis and the aggravation of vasculopathy, PTU was replaced by Iodine-131 (I 131 ) therapy. Induction treatment included oral prednisone 30 mg daily and oral cyclophosphamide 100 mg daily. Symptoms rapidly relieved before discharge. Inflammation markers were normal and MPO-ANCA decreased in 3 weeks after admission. Prednisone was gradually tapered to 7.5 mg daily and at month 10 azathioprine was continued for maintenance. Lessons: RP can overlap with Graves disease and moyamoya disease; comprehensive tests should be performed when admission. When relapsing polychondritis is accompanied with Graves disease, especially when ANCA is positive, PTU should be avoided.